153k views
5 votes
Solve for x.

-15x + 6 = -10x + 16

User Ben Butzer
by
6.7k points

2 Answers

5 votes

Answer:

x = -2

Explanation:

-15x + 6 = -10x + 16

First, subtract 6 from both sides.

-15x = -10x +10

Then Add 10x to both sides.

-5x = 10

Now, divide both sides by -5

x = -2

To check your work substitute the x in the original problem with -2 and they should be equal.

-15(-2) + 6 = 36

-10(-2) + 16 = 36

User AeroHil
by
6.4k points
5 votes

Explanation:

collect like terms

- 15x + 10x = 16 - 6

-5x= 10

x = 10/-5 = -2

User Javeed Shakeel
by
6.4k points